Synchronicity of viral shedding in molossid bat maternity colonies. (8th February 2023) - Hoarau, Axel O. G.; Köster, Marie; Dietrich, Muriel; Le Minter, Gildas; Joffrin, Léa; Ramanantsalama, Riana V.; Mavingui, Patrick; Lebarbenchon, Camille
Abstract: Infection dynamics in vertebrates are driven by biological and ecological processes. For bats, population structure and reproductive cycles have major effects on RNA virus transmission. On Reunion Island, previous studies have shown that parturition of pregnant females and aggregation of juvenile Reunion free-tailed bats ( Mormopterus francoismoutoui ) are associated with major increase in the prevalence of bats shedding RNA viruses. The synchronicity of such shedding pulses, however, is yet to be assessed between viruses but also maternity colonies. Based on 3422 fresh faeces collected every 2–5 weeks during four consecutive birthing seasons, we report the prevalence of bats shedding astroviruses (AstVs), coronaviruses (CoVs) and paramyxoviruses (PMVs) in two maternity colonies on Reunion Island. We found that the proportion of bats shedding viruses is highly influenced by sampling collection periods, and therefore by the evolution of the population age structure. We highlight that virus shedding patterns are consistent among years and colonies for CoVs and to a lesser extent for PMVs, but not for AstVs. We also report that 1% of bats harbour co-infections, with two but not three of the viruses, and most co-infections were due to CoVs and PMVs.